UPAYA MENINGKATKAN HASIL BELAJAR KIMIA MATERI IKATAN KIMIA DENGAN MENGGUNAKAN METODE EXAMPLE NON EXAMPLE PADA PESERTA DIDIK KELAS X MIPA 3 SMA NEGERI 72 JAKARTA - Isnaini Chomsiatun (Bajang Institute, 2022)
This study aims to improve Chemistry learning outcomes with the Example non Example method for Class X MIPA 3 Students at SMA Negeri 72 Jakarta in the 2019/2021 Academic Year, making Chemistry lessons a fun lesson and forming critical thinking characters so that students can solve problems in everyday life day. The problems posed in this study are: